Pengembangan Blade Pemotong Berbasis PLA Hasil 3D Printing dengan Penguat Plat Stainless untuk Meningkatkan Konsistensi Dimensi Pelet pada Mesin Produksi Pakan Ikan - Rian Prasetyo; Ainur Komariah; Suprapto Suprapto; Maria Puspita Sari (Universitas Veteran Bangun Nusantara, 2026)
The cutting blade used in pellet production machines directly affects the dimensional consistency of produced pellets. Polymer-based blades manufactured using 3D printing offer advantages in production cost and fabrication flexibility, but still have limitations in mechanical durability under repeated use. This study aimed to develop a cutting blade made of PLA (Polylactic Acid) using 3D printing technology with a 2 mm stainless steel reinforcement at the blade tip, and to evaluate its effect on pellet length stability in a pellet production machine. The blade was designed using SolidWorks and fabricated using Fused Deposition Modeling (FDM) with a 0.4 mm nozzle, 0.22 mm layer height, 100% infill, 60°C bed temperature, 210°C extruder temperature, and 4500 mm/min printing speed. Testing was conducted using a pellet machine operating at 70 rpm for 6 cycles, with 200 g of feed material per cycle and 8 pellet samples measured in each cycle. The results showed that the full PLA blade experienced an increase in average pellet length from 4.99 mm to 7.05 mm, while the hybrid blade only increased from 3.78 mm to 4.22 mm. One-Way ANOVA results indicated that testing cycles significantly affected pellet length in both the full PLA blade (F = 365.015; p < 0.001) and the hybrid blade (F = 61.255; p < 0.001). The study concludes that stainless steel reinforcement resulted in more stable pellet dimensions during repeated testing, compared to full PLA blades.